2014
DOI: 10.1080/1745039x.2014.992179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles and hydroxyproline, administeredin ovo, on the development of blood vessels and cartilage collagen structure in chicken embryos

Abstract: It has been considered that concentrations of certain amino acids in the egg are not sufficient to fully support embryonic development of modern broilers. In this study we evaluated embryo growth and development with particular emphasis on one of the major components of connective tissue, collagen. Experiments were performed on Ross 308 chicken embryos from 160 fertilised eggs. Experimental solutions of silver nanoparticles (Ag), hydroxyproline solution (Hyp) and a complex of silver nanoparticles with hydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Another study on growing chickens indicated that 20 mg/L Ag NPs decreased the expression of fibroblast growth factor 2 (FGF2) and increased the expression of vascular endothelial growth factor A (VEGFA) at both the mRNA and protein levels in the heart and breast muscle . Intriguingly, up‐regulated expression of FGF2 at the transcriptional and translational levels, and increased blood vessel size, cartilage collagen fibre lattice size and bundle thickness in the Ag NP‐treated chicken embryos were recently reported . FGF2 isoforms are essential in many cardiac pathological conditions, such as cardiac hypertrophy, ischemia‐reperfusion injury and AS.…”
Section: Bio‐toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on growing chickens indicated that 20 mg/L Ag NPs decreased the expression of fibroblast growth factor 2 (FGF2) and increased the expression of vascular endothelial growth factor A (VEGFA) at both the mRNA and protein levels in the heart and breast muscle . Intriguingly, up‐regulated expression of FGF2 at the transcriptional and translational levels, and increased blood vessel size, cartilage collagen fibre lattice size and bundle thickness in the Ag NP‐treated chicken embryos were recently reported . FGF2 isoforms are essential in many cardiac pathological conditions, such as cardiac hypertrophy, ischemia‐reperfusion injury and AS.…”
Section: Bio‐toxicitymentioning
confidence: 99%
“…54 Intriguingly, up-regulated expression of FGF2 at the transcriptional and translational levels, and increased blood vessel size, cartilage collagen fibre lattice size and bundle thickness in the Ag NP-treated chicken embryos were recently reported. 55 FGF2 isoforms are essential in many cardiac pathological conditions, such as cardiac hypertrophy, ischemia-reperfusion injury and AS. Moreover, VEGFA has specific roles in regulating the cardiac muscle capillaries and the early development of the vasculature.…”
Section: Bio-toxicitymentioning
confidence: 99%
“…It has also been reported that Ag NPs, glutamine (25 mg/ml), and a complex of Ag NPs and glutamine do not affect embryos. However, the muscle percentage in the group treated with Ag NPs+glutamine is significantly increased compared to that in treated with Ag NPs alone [36]. Similarly, in ovo injection of Gly and Pro might have resulted in higher body weights of chicks in the 14 th day injection group.…”
Section: Body Weightmentioning
confidence: 86%
“…It has also been reported that Ag NPs, glutamine (25 mg/mL), and a complex of Ag NPs and glutamine do not affect embryos. However, the muscle percentage in the group treated with Ag NPs+glutamine is significantly increased compared to the group treated with Ag NPs alone [1]. Similarly, in ovo injection of Gly and Pro might have resulted in higher body weights of chicks in the 14th day injection group.…”
Section: Body Weightmentioning
confidence: 88%
“…Nutrition by in ovo injection is a new methodology for directly supplying additional nutrients and bio-active compounds, mainly amino acids, and carbohydrates into the fertilized embryo particularly during incubation time to promote the growth and development of muscles during embryogenesis. Moreover, the hatching rate and pectoral muscle growth were increased by nutrients by in ovo injection [1]. This early nutritional strategy offers the promise of sustaining progress in production efficiency and welfare of commercial poultry.…”
Section: Introductionmentioning
confidence: 99%